The Implementation of Democratic Education in Islamic Religious Education (PAI) Learning to Shape the Creative Character of Students in Madrasah Aliyah - Rosyada Ayu Fatimah; Arif Rahman; Betty Mauli Rosa Bustam (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Character education is an important issue in forming a young generation with integrity and creativity. However, the lack of emphasis on this aspect in learning, especially at the madrasah level, is still an obstacle. This study aims to identify the implementation of democratic education by teachers in Islamic Religious Education (PAI) learning, explain the process of forming students' creative character, and analyze its impact. This study uses a qualitative approach with a case study method at MA Al-Ichsan Kulon Progo. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The results showed that teachers implemented democratic education by creating a participatory, reflective, and collaborative learning atmosphere. Democratic education has proven effective in forming students' creative character as reflected through aspects of moral knowing, moral feeling, and moral action. The impact is seen in increasing students' independence, creativity, and adaptability in PAI learning.